Construção e validação de cartilha educativa para prevenção da transmissão vertical do HIV - Lima, Ana Carolina Maria Araújo Chagas Costa (2014)
The study aimed to construct and validate the contents and appearance of an educational booklet for the prevention of vertical transmission of HIV. This was a methodological research. To conduct the study, we followed the steps: submission of the project to the research ethics committee; literature survey; development and validation of material by expert judges and representatives of the target audience. Initially it was implemented the bibliographic from 15 papers of the Ministry of Health of Brazil about the care that mothers should have for the prevention of mother to child transmission of HIV. The booklet developed was titled "How to prevent transmission of HIV from mother to child? Get inside!", addressing care for the prevention of vertical transmission in pre-natal, childbirth and postpartum. In the preparation of the primer stage, the texts were compiled from the information gathered in the literature and consulted one expert in design for making the figures. Nine judges were selected to validate appearance and content, according to pre-established criteria and to validate appearance by the target audience, 30 women were selected, with 23 pregnant and 7 postpartum HIV positive captured in two public hospitals in the city of Fortaleza - Ce. The period of data collection with judges and women occurred between August and December 2013. To collect data, two instruments, one directed to the judges and one for the target audience, were used. For the validity of the content of the booklet, we used the Content Validity Index ( CVI ), with a cutoff of 0.78. For the validity of appearance by the judges and audience were considered validated items that obtain a minimum level of agreement of 75 % for positive responses. The suggestions and opinions were collated and presented in tables. The educational booklet in the study was the first to be developed within the theme and showed up as a validated material, since it showed good overall CVI of 0.87 and excellent level of agreement between judges, ranging from 91.1% to 100% and between the audience that ranged from 93.3% to 100% . Given the suggestions and contributions during the validation process, the booklet has undergone modifications, adjustments and additions to make it more effective, so that the playbook went from 20 pages to 28 in the final version. It is believed that the use of this material with HIV positive women from pre-conception period to the postpartum facilitate nursing practice, because that is illustrated in a technology capable of promoting dialogue between professionals and women, facilitate the acquisition of knowledge and provide the empowerment of women, HIV positive pregnant women and postpartum women.